2011
DOI: 10.1007/s11368-011-0371-2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of Fe(III)-reducing microorganisms in rice paddy soil: enrichment cultures with different short-chain fatty acids as electron donors

Abstract: Purpose Microbial ferric iron reduction is an important biogeochemical process in nonsulfidogenic anoxic environments, yet the structure of microbial communities involved is poorly understood because of the lack of a functional gene marker. Here, with ferrihydrite as the iron source, we characterized the potential Fe(III)-reducing bacteria from the paddy soil in the presence of different short-chain fatty acids, formate, acetate, propionate, pyruvate, succinate, and citrate. Materials and methods Enrichment cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…represents 0.07%, 0.42%, and 0.92% of the microbial community at 0−5 cm and 20−25 cm at spot B and at 0−15 cm at spot C, respectively. Additionally, Clostridium spp., known to reduce Fe(III) through fermentation 26 or respiration, 27 is also found at 100−105 cm at spot B (0.61%). Moreover, iron-oxidizing bacteria from the Crenothrix genus 28 are identified in samples from spot B at 0−5 cm (1.4%) and at 20−25 cm (3.95%) and from spot C at 0−15 cm (0.33%) (Figure 4).…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…represents 0.07%, 0.42%, and 0.92% of the microbial community at 0−5 cm and 20−25 cm at spot B and at 0−15 cm at spot C, respectively. Additionally, Clostridium spp., known to reduce Fe(III) through fermentation 26 or respiration, 27 is also found at 100−105 cm at spot B (0.61%). Moreover, iron-oxidizing bacteria from the Crenothrix genus 28 are identified in samples from spot B at 0−5 cm (1.4%) and at 20−25 cm (3.95%) and from spot C at 0−15 cm (0.33%) (Figure 4).…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…As a class one carcinogen, arsenic in the soil can present a significant risk to humans through the food chain after its high uptake into rice plants. It has been estimated that rice is the major dietary source of As for populations with rice as the staple food (Meharg and Rahman 2003;Mondal and Polya 2008;Zhu et al 2008;Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that genomics data can be integrated into biogeochemical model to predict environmental changes modulated by diverse functional microbes (Reed et al 2014). The importance of microbe-mediated iron redox changes in controlling the biogeochemistry of elements in the environment, particularly in sediments and wetland, is well established (Melton et al 2014), Paddy soils are subjected to regular dry-wet cycles, and longterm paddy cultivation will lead to the accumulation of amorphous iron, which is a common terminal electron acceptor (Ding et al 2015;Li et al 2011). Therefore, understanding the diversity and distribution of Geobacteraceae, a major group of microbes involved in dissimilatory iron reducers in paddy soils, at large scale will be indispensible in predicting the biogeochemical cycling of contaminants and nutrients.…”
Section: Discussionmentioning
confidence: 99%